Digital Transformation in Emerging Fashion Economies: A Qualitative Review of CAD/CAM Adoption and Its Implications for Design (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the role of Computer Aided Design and Computer Aided Manufacturing technologies in driving digital transformation within Bangladesh’s apparel industry. The research adopts a systematic literature review approach based on existing academic and industry sources. The analysis focuses on three key areas. These are design transformation, production efficiency, and sustainability outcomes. The findings show that digital tools improve design flexibility and accuracy.They also enhance production efficiency through faster processes and better coordination. In addition, these technologies support sustainability by reducing material waste and improving resource use. However, the impact of digital transformation depends on factors such as infrastructure, investment, and skill availability. The study highlights that adoption is uneven across firms in Bangladesh. Overall, the research provides an integrated understanding of how CAD and CAM technologies influence the apparel sector in an emerging economy. The study also offers insights for future research and industry practice.